A STUDY OF HOW LANGUAGE ANXIETY AND FIRST LANGUAGE INFLUENCE AFFECT THE SPEAKING SKILLS IN SECOND LANGUAGE LEARNING - Kadar, Annisa Syauqina (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2024)
Second language acquisition (SLA) is a multifaceted process, and speaking proficiency is often one of the most challenging aspects for learners. This study investigates the impact of two critical factors language anxiety and first language (L1) transfer on the speaking skills of second language learners, with a focus on Indonesian learners of Mandarin. Using a descriptive qualitative approach, the study explores how anxiety and L1 transfer shape learners' ability to speak confidently and fluently. Data were collected through semi-structured, in-depth interviews with five participants who have experienced both language anxiety and L1 transfer challenges. The findings reveal that language anxiety significantly impedes fluency, leading to hesitation, cognitive interference, and avoidance behavior. Similarly, L1 transfer had both positive and negative effects on speaking skills, with pronunciation and sentence structure often influenced by the learners' native language. The interaction between language anxiety and L1 transfer created a compounded effect, with negative transfer exacerbating anxiety and further hindering speaking performance. Positive L1 transfer, however, helped to alleviate anxiety and facilitated smoother speech. The study concludes by emphasizing the importance of addressing both emotional and linguistic challenges in SLA, suggesting that educators should adopt strategies to manage anxiety while leveraging positive L1 transfer to enhance speaking proficiency